2003
DOI: 10.1128/jcm.41.10.4642-4646.2003
|View full text |Cite
|
Sign up to set email alerts
|

Human Metapneumovirus Infection in the Canadian Population

Abstract: Human metapneumovirus (hMPV), a newly discovered paramyxovirus, has been associated with acute respiratory tract infections (ARIs) ranging from upper ARIs to severe bronchiolitis and pneumonia. Important questions remain on the contribution of hMPV to ARIs and its impact on public health. During the 2001-2002 season, we conducted a collaborative study with four provincial public health laboratories to study the prevalence of this new virus in the Canadian population. A total of 445 specimens were collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
131
2
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 150 publications
(153 citation statements)
references
References 17 publications
(28 reference statements)
12
131
2
6
Order By: Relevance
“…[22][23][24] Therefore, clinicians can use surveillance data, such as NREVSS, to help identify HMPV seasonality and help prioritize HMPV testing in patients with respiratory symptoms. As laboratory recruitment into NREVSS and PCR use continue to increase throughout the United States, future NREVSS data should be able to more reliably allow for more detailed analyses, including regional HMPV trends and outbreak occurrence, similar to those for RSV and influenza.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Therefore, clinicians can use surveillance data, such as NREVSS, to help identify HMPV seasonality and help prioritize HMPV testing in patients with respiratory symptoms. As laboratory recruitment into NREVSS and PCR use continue to increase throughout the United States, future NREVSS data should be able to more reliably allow for more detailed analyses, including regional HMPV trends and outbreak occurrence, similar to those for RSV and influenza.…”
Section: Discussionmentioning
confidence: 99%
“…Since its initial description, hMPV has been identified as a leading cause of LRTIs in previously healthy infant and child outpatients [11]. The incidence of hMPV-associated LRTI in young children varies with geographical location and time of year, and can range from 5 to 15% [12][13][14][15][16][17][18]. However, higher rates have also been reported [19,20].…”
mentioning
confidence: 91%
“…The primers used for amplification and sequencing were based on the hMPV F gene sequence, ie, MPVF1f (5Ј-CTTTGGACTTAATGA-CAGATG-3Ј) and MPVF1r (5Ј-GAGAAGAGCTGGGTAGAAG-3Ј), which were used to amplify a 450-base pair fragment of the F gene. 2 Appropriate positive and negative control assays were performed, and the amplified PCR product was confirmed with sequence analysis. Phylogenetic analysis of the F gene sequence from the infant's isolate revealed that the causative virus was similar to previous Canadian isolates of hMPV (Fig 2).…”
Section: Case Reportmentioning
confidence: 99%